FRI0211 The role of NKG2D, CX3CR1 and TLR4 in the pathogenesis of giant cell arteritis. (23rd January 2014) - Al-Massad, J.; Dejaco, C.; Duftner, C.; Ness, T.; Haller, H.; Schirmer, M.; Wagner, A.D.
Abstract : Background: Pattern recognition receptors like NKG2D [1] and TLR4 [2] together with chemokine receptors like CX3CR1 [3] are important mediators of innate immunity. Objectives: The study was performed to assess the expression of NKG2D, CX3CR1 and TLR4 on T-cells in temporal arteries from patients with giant cell arteritis (GCA) and to compare findings with results from peripheral blood analysis. Methods: Temporal artery biopsies were obtained from 19 patients diagnosed with GCA and from 9 patients without GCA. For analysis of peripheral blood T-cells from consecutive patients with GCA (n=16) and PMR (n=78) were investigated. Immunohistochemical staining was performed on paraffin-embedded temporal arteries using anti-CD3, anti-CD4, anti-CD8 and anti-NKG2D (monoclonal antibodies) as well as anti-CX3CR1 and anti-TLR4 (polyclonal antibodies) according to a routine protocol. For assessment of circulating T-cells anti-CD4, anti-CD8, anti-CD28, anti-NKG2D, anti-CX3CR1 and anti-TLR4 mAbs were used and cells were analyzed by flow cytometry. Statistical analysis was performed using SPSS. Results: Immunohistochemical analysis of temporal arteries confirmed CD4 + T-cells as the dominant T-cell population in GCA showing a ratio of 70/30 compared with CD8 + T-cells. Most pronounced expression of NKG2D was shown in the media and adventitia compared to intima. Immunofluorescence double-staining confirmed the expression of NKG2D on every fifth CD3 + T-cell especially in the adventitia near the vasa vasorum. The expression of NKG2D showed no dependence on a therapy with glucocorticoids over time. The chemokine receptor CX3CR1 and the toll-like receptor TLR4 accumulated in the adventitia of temporal arteries. Likewise CX3CR1 + CD3 + and TLR4 + CD3 + T-cells were detected on every fifth and third T-cell, respectively. Biopsies of the control group compared to the GCA group showed statistically significant lower numbers of NKG2D-, CX3CR1- and TLR4-positive cells as determined by student's t-test. In peripheral blood analysis we found NKG2D, CX3CR1 and TLR4 particularly on senescent CD4 + CD28 - T-cells (NKG2D: 23.1±24.0% out of CD4 + CD28 - cells, p<0.001 compared to CD4 + CD28 + cells; CX3CR1: 62.7±22.8%, p<0.001 TLR4 4.7±11.1%, p<0.001) whereas expression was negligible on CD4 + CD28 + . In the CD8 + T-cell subset, NKG2D was expressed in >95% of cells with comparable levels between CD8 + CD28 - and CD8 + CD28 + T-cells. CX3CR1 was present in the CD8 + CD28 - subset only (65.8±20.2%, p<0.001 compared to CD8 + CD28 + cells) and TLR4 was not expressed on CD8 + T-cells. Conclusions: The expression of NKG2D is indicative of co-stimulative activity. The finding of CX3CR1 on T-cells close to vasa vasorum might be in accordance with leucocyte extravasation. The expression of TLR4 on T-cells most likely with the loss of the co-stimulatory surface glycoprotein CD28 represents a link between the adaptive and the innate immune system and might be indicative for an alternative signaling pathway in the pathophysiology of GCA. References: Maasho K et al. J Immunol, 2005; 174: 4480-4484. Raffeiner B et al. Arthritis Res Ther. 2005; 7:1412-1420. Umehara H et al. Arterioscler Thromb Vasc Biol. 2004; 24: 34-30. Disclosure of Interest: None Declared